BIBLIOMETRIC ANALYSIS OF ARTICLES IN THE CONTEXT OF PROPOLIS AND CHILDREN - Merve KESKIN; Selin IKIZ (Journal of Animal and Plant Sciences, 2025)
Propolis is an important natural product and it positively affects health conditions with its bioactive compounds. Using propolis is getting popular in adults but, parents who want to improve their child’s health should be used it carefully and consciously due to its side effects. In this respect, it is very important to examine the studies in the context of propolis and children to reveal the trends of the studies on the subject to understand the current situation and guide future studies. In this study, research and review articles in the context of propolis and children were examined. The research data were obtained from the Web of Science (WOS) database and the keywords "propolis*" and "child*" were entered in the relevant search section. The star symbol was used after the main word to include different word variations used in the articles’ title, abstract, and author keywords. Within the scope of the research, a total of 140 articles on the concepts of propolis and child were identified. The articles were analyzed using R- programmer, Bibliometrix R-package. During the analysis, the articles were analyzed according to the year of publication, journals, keywords, countries, and frequently used concepts. The data showed that studies on propolis and child have increased since 1981. It was determined that the most publications on the subject were made in Italy (n= 80), Iran (n= 78), and China (n= 67) and that these countries carried out the most articles between 2024 and 2025. It was observed that the journals with the highest number of publications on the subject were Evidence-Based Complementary and Alternative Medicine (n= 6), Complementary Therapies Medicine (n= 5), and International Journal of Early Childhood Special Education (n= 4). It was determined that the most popular keywords used in the articles were propolis, children, honey, caffeic acid phenethyl ester, and oxidative stress. In line with the results obtained from the research, it is concluded that more studies should be carried out with different variables about propolis and children because the studies on the subject are quite limited.
Keywords: propolis; child; health; bibliometrics; Biblioshiny